POLITICO-LEGAL PAGEANTRY AND LIFE IN ARAVIND ADIGA’S THE WHITE TIGER - Kumari, Suman; Sood, Reetika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corruption deters growth and development and consequently aggravates poverty and inequality. The ugly face of India hidden behind decent, equitable, progressive economic power with unbiased growth, indiscriminate equity-based programs and an efficient politico-legal system has been scathingly attacked by Adiga in this novel. The poor subalterns amidst these corrupt practices become a scapegoat to the corrupts and a wave of anger remains lurking inside them. The fluttering of sufferers to make themselves free from the suffocative rooster coops intermingled with misguided intelligence and desire to hit back against the violence imposers pose a threat to the nation’s integrity and age-old value system. It is a grave concern that the sufferers are too adopting the corrupt strategy of ‘survival of the fittest’ in terms of money justifying the rationality of corrupt ways of earning it.